KEMISKINAN DI PROVINSI SULAWESI BARAT DAN DETERMINANNYA - Dwi Ardian (BPS Kalimantan Timur, 2025)
Poverty in Sulawesi Barat Province has experienced a slow decline, and has even consistently increased since 2021-2024, placing Sulawesi Barat poverty always above national poverty which tends to decline to single digits. The role of the agricultural sector and informal sector businesses which dominate with an average income below the UMP is thought to be the main factor causing poverty. Apart from that, health factors and educational factors are also thought to have quite an influence on people's productivity in meeting their basic needs. Thus, this research will examine the relationship between GRDP in the agricultural sector, employment, health and education indicators to poverty in Sulawesi Barat Province. The data used is secondary data that has been released by BPS-Statistic of Sulawesi Barat Province, including poverty levels, GRDP based on constant agricultural sector prices, open unemployment rates, life expectancy, and average years of schooling, in 6 districts during the 2015-2024 period. Data were analyzed using panel data regression. The GRDP variable based on constant prices in the agricultural sector has a negative and significant influence on poverty. The variable open unemployment rate (TPT), life expectancy (UHH), and average years of schooling (RLS) insignificant influence on poverty. The coefficient of determination (R2) reached 64.62 percent, indicating that the independent variable is strong enough to explain the dependent variable. Seeing the crucial role of the agricultural sector in Sulawesi Barat, it is necessary to increase productivity in various ways such as building supporting infrastructure, applying modern technology, and so on.